The Role of Innovative Leadership in Driving Educational Management Transformation - Halimah Halimah; Syafruddin Syafruddin; Novi Indah Earlyanti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Through an in-depth literature review, this literature study aims to analyze the role of innovative leadership in supporting educational management transformation. This research is qualitative research that uses a literature study approach. The main data sources are scientific literature, books, journal articles, and academic documents related to the role of innovative leadership in transforming educational management. Library studies collect data through searches for relevant literature using academic databases, digital libraries, and trusted sources. Data analysis in this study involved the synthesis and interpretation of relevant literature. The researcher identified major themes, key concepts, and significant findings from the literature. The analysis process includes compiling data, grouping information, and interpreting the meaning of the literature accessed. The research results state that innovative leadership plays a vital role in shaping and directing the transformation of educational management amidst the dynamics of development and change in the contemporary era. Innovative leadership has a very important role in driving the transformation of educational management. By creating a culture of innovation, developing adaptive management strategies, taking measured risks, motivating those around them, and managing change wisely, innovative leaders shape the future of education that is more dynamic, inclusive, and relevant.